Two phase flow visualization in evaporator tube bundles using experimental and numerical techniques - Schlup, Jason (Kansas State University, 2013)
This research presents results from experimental and numerical investigations of two-phase flow pattern analysis in a staggered tube bundle. Shell-side boiling tube bundles are used in a variety of industries from nuclear power plants to industrial evaporators. Fluid flow patterns in tube bundles affect pressure drop, boiling characteristics, and tube vibration. R-134a was the working fluid in both the experimental and computational fluid dynamics (CFD) analysis for this research. Smooth and enhanced staggered tube bundles were studied experimentally using a 1.167 pitch to diameter ratio. The experimental tube bundles and CFD geometry consist of 20 tubes with five tubes per pass. High speed video was recorded during the experimental bundle boiling. Bundle conditions ranged in mass fluxes from 10-35 kg/m[superscript]2.s and inlet qualities from 0-70% with a fixed heat flux. Classification of the flow patterns from these videos was performed using flow pattern definitions from literature. Examples of smooth and enhanced bundle boiling high speed videos are given through still images. The flow patterns are plotted and compared with an existing flow pattern map. Good agreement was found for the enhanced tube bundle while large discrepancies exist for the smooth tube bundle. The CFD simulations were performed without heat transfer with non-symmetrical boundary conditions at the side walls, simulating rectangular bundles used in this and other research. The two-phase volume of fluid method was used to construct vapor interfaces and measure vapor volume fraction. A probability density function technique was applied to the results to determine flow patterns from the simulations using statistical parameters. Flow patterns were plotted on an adiabatic flow pattern map from literature and excellent agreement is found between the two. The agreement between simulation results and experimental data from literature emphasizes the use of numerical techniques for tube bundle design.
Keywords: Tube bundle; Computational fluid dynamics; Flow visualization; Mechanical Engineering (0548)